Comparative Analysis of Government Function Expenditure before and during Regional Elections by Incumbents and Non-Incumbents in Sumatera - Faizal Amin; Eka Dewi Anggraini (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to analyze the impact of regional elections before and during regional elections by incumbents and non-incumbents. Variables observed include spending on the function of education, health, economy and social protection. This study compares the budget expenditure function before the election and at the time of the election which was attended by incumbent and non-incumbent regional heads. The comparison is done by comparing the average proportion of shopping before and at the time of the election using the paired sample t-test. The results showed that there were differences in the allocation of expenditures for the education function, expenditures on health functions, expenditures on economic functions, and expenditures on social protection functions between the period before and during the election.